2017
DOI: 10.17221/16/2016-swr
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and accumulation of heavy metals in sediments of the northern part of mangrove in Hara Biosphere Reserve, Qeshm Island (Persian Gulf)

Abstract: ZareZadeh R., Rezaee P., Lak R., Masoodi M., Ghorbani M. (2017): Distribution and accumulation of heavy metals in sediments of the northern part of mangrove in Hara Biosphere Reserve, Qeshm Island (Persian Gulf ). Soil & Water Res., 12: 86−95.The mangrove of Hara Biosphere Reserve, stretching over 100 thousand hectares in the southern coast of Iran and in the northwest of Qeshm Island, belongs to the most important and largest mangroves in the Middle East. Twenty sedimentary samples were collected and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…The average concentration of Cu (43.06 µg g -1 ) was higher in comparison to the most studies carried in coastal areas of the Arabian Gulf and the Red Sea. Similarly, the average concentrations of Cr, Cd and Ni were also found to be greater than the previous studies in the Arabian Gulf [49,50]. In addition, the average concentration of Pb (26.61 µg g -1 ) was higher than those recorded in some areas reported in the previous studies except for Shriadah [49] and Usama et al [51] in Abu-Dhabi and Farasan Island, respectively.…”
Section: Sediment Characteristicscontrasting
confidence: 46%
See 1 more Smart Citation
“…The average concentration of Cu (43.06 µg g -1 ) was higher in comparison to the most studies carried in coastal areas of the Arabian Gulf and the Red Sea. Similarly, the average concentrations of Cr, Cd and Ni were also found to be greater than the previous studies in the Arabian Gulf [49,50]. In addition, the average concentration of Pb (26.61 µg g -1 ) was higher than those recorded in some areas reported in the previous studies except for Shriadah [49] and Usama et al [51] in Abu-Dhabi and Farasan Island, respectively.…”
Section: Sediment Characteristicscontrasting
confidence: 46%
“…Biosphere Reserve, Iran [50] and Farasan Island [51] (Table 3). Recently, trace elements were studied in the same area and it was found that data obtained through the current study could be comparable with previous studies [15,22,23].…”
Section: Sediment Characteristicsmentioning
confidence: 99%
“…They showed there is a significant correlation between organic carbon and carbonate levels with metal concentration. Also, Karbassi and Amirnezhad (2004), Mooraki et al (2009), Hosseini et al (2014a, b), Vaezi et al (2015) and ZareZadeh et al (2017) have similar results with present study in the sediment contaminated from Persian Gulf, south Iran.…”
Section: Resultssupporting
confidence: 88%
“…There are different studies that showed geoaccumulation index values for Pb and Se was higher than 5 (strongly polluted) in the sediment from Persian Gulf (Karbassi et al 2008; Saeedi and Karbassi 2006; Hosseini et al 2014b; Raeisi Sarasiab et al 2014; Nowrouzi and Pourkhabbaz 2014;Vaezi et al 2015; ZareZadeh et al 2017). Moore et al (2009) reported that that geoaccumulation index values were 4.5 for Pb in and 2.8 for Se in the Maharlu Aaline Lake, Iran.…”
Section: Resultsmentioning
confidence: 98%
“…In developing countries in general and in Turkey in particular, ecotoxicological assessments and studies to determine background values are scarce, especially for sediments. Therefore, for the purposes of this study, globally accepted SQGs were used instead of ecotoxicological results [37][38][39][40] , and Average Shale Values (ASVs) were used instead of background values [41][42][43][44][45] . SQGs include criteria designed to assess sediment quality and the ecological risks associated with heavy metals 46 .…”
Section: Sediment Quality Guidelines (Sqgs)mentioning
confidence: 99%